Ekspansi Politik Dinasti Jokowi: Peirce's Semiotic Study on the cover of Tempo Magazine - Fatiya Zahida; Nasution, Nadya Amalia (Jurnal Audiens, 2024)
Media coverage plays a crucial role in shaping public perception of political dynamics in Indonesia, particularly through visual representations. The increasing concerns about political dynasties and their impact on democratic processes have become a significant issue in Indonesian politics.  This research applies Charles Sanders Peirce's semiotic theory to analyze the cover of Tempo magazine using qualitative research. The study aims to reveal the essential messages and ideological constructions conveyed to the audience by examining the signs, symbols, and meanings embedded in the cover design. The analysis focuses on the cover of Tempo magazine's 02 June 2023 edition, "Political Expansion of the Jokowi Dynasty." Through a detailed semiotic study, this research reveals how Tempo magazine utilises visual and textual elements to communicate its editorial stance, attract readers, and reflect contemporary socio-political issues. The results of the study are based on the analysis of Peirce's semiotic theory, namely that Tempo magazine, through the illustrations on its cover, succeeded in conveying a message about the political expansion of the Jokowi dynasty through the use of solid symbols and effective visual signs, including analysis through icons, indexes, and symbols. These results significantly contribute to a deeper understanding of media semiotics and how magazine covers can influence public perception.